Inter-American Cooperation at a Crossroads
XXXIV, 278 p.
Keywords: Fifteen years after the first Summit of the Americas, the world and the Americas have changed enormously. Competing strategies for economic development and political representation have shattered the hemispheric consensus of the 1990s. This book analyzes these developments and points towards a future for inter-American co-operation.